Short Arabic Plays - Michelle Hartman (International Institute of Islamic Thought, 2004)
Like most of the other anthologies edited by Salma Khadra Jayyusi, Short Arabic Plays is a collection of translated Arabic literary works focused around one particular genre. This anthology, part of Jayyusi’s Project for the Translation of Arabic (PROTA), will bring attention to a dynamic, but understudied, genre of Arabic literature. This diverse collection consists of 20 short plays by 15 playwrights, demonstrating the breadth of the genre and its interest not only to scholars and specialists, but also to those concerned with literature more generally. One problem with this particular anthology, however, is that Jayyusi’s seven-page editor’s introduction barely manages to explain the impetus behind the project, make her acknowledgments and outline the major themes in short plays in general – let alone contextualize the plays included in this volume. Although it includes short biographies of the editor, contributors, and translators (after a brief glossary of Arabic words), there are no introductions to the individual works or even such bibliographic indications as their original titles and dates of publication. In contrast, other anthologies by Jayyusi – for example, Modern Arabic Poetry: An Anthology (Columbia University Press: 1987) and Anthology of Modern Palestinian Literature (Columbia University Press: 1992) – are accompanied by useful and lengthy introductions written by Jayyusi herself, as well as brief introductions to each individual contribution. Likewise, the anthology most closely related to this one, Modern Arabic Drama: An Anthology, coedited with Roger Allen ...